Pengaruh Penerapan Media Wordwall terhadap Hasil Belajar Siswa pada Materi Kalimat Majemuk di Tingakat Sekolah Dasar - Fatimah Azzahro; Emy Yunita Rahma Pratiwi (IJPSE Indonesian Journal of Primary Science Education, 2026)
This study stemmed from the issue of inadequate student performance in compound sentence content within Indonesian language education. The primary challenges encountered by students were comprehending sentence structure and using conjunctions accurately. This situation underscores the need for innovation in educational media, since the limited use of interactive media has adversely affected student engagement and comprehension. Consequently, a medium is required that may capture attention while proficiently augmenting pupils' comprehension. Wordwall, an interactive digital platform, provides a range of customizable educational games tailored to certain teaching materials.This research seeks to investigate the impact of Wordwall media on student learning outcomes for compound sentence content at the elementary school level. A quantitative methodology was used, using a pre-experimental design including a one-group pretest-posttest design. This research had a total of 30 students as participants. Data were gathered via an objective assessment tool delivered before to and during the intervention to evaluate learning results. Subsequently, the data were examined using the Shapiro-Wilk normality test and the Wilcoxon test.The study results indicated that the mean posttest score (89.87) was substantially greater than the mean pretest score. The Wilcoxon test findings corroborated this conclusion with a significance value of 0.000, which is below the 0.05 significance threshold. Consequently, it can be stated that the use of Wordwall media positively and significantly enhances student learning results. This medium has shown efficacy and is deserving of consideration as an innovative alternative learning resource in primary education.